Prevalence of tobacco use and effectiveness of physician’s brief advice on tobacco cessation in the context of type 2 diabetes mellitus outpatients: A cross-sectional study - N S Javadekar; N P Ghate; A S Bodas; K M Shelgikar; A P Joshi (Industrial Psychiatry Journal)
Background: Tobacco use is the largest preventable risk of non-communicable diseases (NCDs). Moreover, tobacco use interferes with glycaemic control, and there is a proven link between smoking and diabetes complications. Aim: This cross-sectional study investigates the prevalence of tobacco use and the effect of advice about quitting and its impact at one-month and one-year follow-ups in outpatient type 2 diabetics. Materials and Methods: Type 2 diabetes patients attending physician OPD in tertiary care hospitals were interviewed using a questionnaire based on Global Adult Tobacco Survey (GATS) 2, India. They also received the National Toll-Free Quitline Number 1800112356 and the M Cessation no. 011-22901701. The free tobacco cessation clinic details at the government hospital in Pune were also shared, in case patients wanted to attend these facilities. Results: The prevalence of tobacco use was 19% (present and former tobacco usage), wherein smoking contributed 9.0%, smokeless tobacco (SLT) contributed 7.5%, and dual use contributed 2.5%. The highest use was observed in the seventh decade. More women than men used smokeless tobacco. Poly SLT use and dual tobacco use – smoking and smokeless tobacco products, use of areca nut with SLT was also observed. Following brief physician advice, 27.2% quit tobacco usage at one-year follow-up. Conclusion: A history of tobacco use needs to be asked to all type 2 diabetes mellitus (DM) patients in each visit, documenting it, explaining the importance of quitting tobacco in the context of diabetes, and advising to quit tobacco, even to elderly patients. If all the physicians in the health system offer quit advice to all the tobacco users, many patients are likely to quit tobacco.